Analyzing Character Education Values in Textbook English on Target - Melati Ayuna Sari Puteri; Kismullah Abdul Muthalib; Hendra Heriansyah (Universitas Syiah Kuala, 2023)
The use of a textbook plays an important role in the process of teaching and learning because it functions as a source of learning for both teachers and students. Previous studies showed that a textbook is considered good if it contains character values that can significantly build students’ character. In relation to this, the aim of this study is to highlight character education values that contain on an English textbook entitled ‘English on Target’. For this purpose, a document analysis study was descriptively undertaken as the research method to collect the data by analyzing seven out of eight chapters of the textbook. The research findings revealed that there were seventeen values of character education found such as respect, responsibility, honesty, nationalism, democracy, peace, and so forth. In addition, responsibility was the most frequent value found from each book chapter analyzed. While, the value of tolerance was not discovered in the textbook. In conclusion, this book has met one of the expected standards about textbook writing according to the guidance of 2013 Curriculum article 3 of the Law of the Republic of Indonesia about the National Education System Number 20 of 2003, which states that textbooks used in schools should incorporate character education values as an effort to build student character.